The Influence of Sales Promotion and Personal Selling on the Interest of Buying Wedding Package at ICE BSD Tangerang Selatan - Shafira Nindita; Tri Djoko Sulistio; Michaela Michaela (Journal Hotspot, 2021)
One of the antiquities of tourism is that MICE have benefit from various parties as well as the Indonesia Convention Exhibition which is the largest exhibition building in Southeast Asia. Many people have rented rooms especially for weddings at ICE BSD. In this case the existence of an interest in buying on a wedding package, can not be separated with sales promotion activities and personal selling carried out at the company and it is important to be owned by the company in terms of attracting interest in buying a wedding package. Therefore, the authors conducted research to determine how much influence the sales promotion and personal selling carried out at ICE BSD on the purchase intention of wedding package. The method used is descriptive quantitative, the data obtained from the distribution of questionnaries totaling 88 respondents. The sample collection method uses non-probability sampling technique. Data collection is done by distributing questionnaries using a Likert scale online using Google Forms. Analysis of the data in the study using SPSS. This study used a simultaneous test with 2 independent variables and 1 dependent variable. Likert scale uses with 4 scores. The results of the analysis through the test of determination show that sales promotion and personal selling variables have an effect on buying interest by 52,9% while the remaining 47,2% is influenced by other factors not examined in this study.